(untitled) (Anclajes, 2024)
In Libro centroamericano de los muertos (2018) Balam Rodrigo presents the drama of Central American migrant communities on their journey through Mexican territory towards the United States. The poet from Chiapas resorts to intertextual procedures such as the palimpsest to denounce the systematic violation of human rights in Central American communities, from the time of the conquest to the present day, by taking up documents such as fray Bartolomé de las Casas’ Brevísima relación de la destrucción de las Indias, to expose the suffering of contemporary migrant populations. The poem expresses the torture, kidnapping, rape, dismemberment, and disappearances suffered by migrants on their journey on La Bestia (the popular name for the cargo train network that transits through Mexico), so that the violated and deceased body can be presented as a space of domination, erasure and difference.